2023
DOI: 10.3390/nano13020335
|View full text |Cite
|
Sign up to set email alerts
|

Aramid Nanofiber/XNBR Nanocomposite with High Mechanical, Thermal, and Electrical Performance

Abstract: Aramid nanofibers (ANFs) were successfully produced by deprotonation of Kevlar fiber followed by grafting epichlorohydrin in dimethyl sulfoxide solution. The ANFs were then incorporated into carboxylated acrylonitrile butadiene rubber (XNBR) by means of latex blending, followed by vulcanization. The interaction between ANFs and XNBR, and the effects of ANFs on the mechanical strength, dielectric properties, and thermal stability of ANF/XNBR nanocomposites were investigated. The results revealed that hydrogen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…They have been widely explored as potential materials catering to the increasing demands for protective clothing, industrial vehicles, and construction applications. As previously reported, para-AMFs are able to be exfoliated into poly­( p -phenylene terephthalamide) (PPTA) nanofibers (para-ANFs) experiencing deprotonation with the assistance of dimethyl sulfoxide/potassium hydroxide (DMSO/KOH) solution. For meta-AMFs, the deprotonation environment is varied to be the dimethylacetamide/lithium chloride (DMAC/LiCl) system for the disconnection of the hydrogen bond between the poly­( m -phenylene isophthalamide) (PMIA) molecular chains. , The ANFs inherit the majority of superior properties from AMFs including high-temperature resistance, dielectric insulation, and mechanical strength. With the reduced scale of ANFs being a few tens of nanometers, various functional architectures are feasible including 1D additives, 2D self-assembled films, as well as 3D network structures. …”
Section: Introductionmentioning
confidence: 99%
“…They have been widely explored as potential materials catering to the increasing demands for protective clothing, industrial vehicles, and construction applications. As previously reported, para-AMFs are able to be exfoliated into poly­( p -phenylene terephthalamide) (PPTA) nanofibers (para-ANFs) experiencing deprotonation with the assistance of dimethyl sulfoxide/potassium hydroxide (DMSO/KOH) solution. For meta-AMFs, the deprotonation environment is varied to be the dimethylacetamide/lithium chloride (DMAC/LiCl) system for the disconnection of the hydrogen bond between the poly­( m -phenylene isophthalamide) (PMIA) molecular chains. , The ANFs inherit the majority of superior properties from AMFs including high-temperature resistance, dielectric insulation, and mechanical strength. With the reduced scale of ANFs being a few tens of nanometers, various functional architectures are feasible including 1D additives, 2D self-assembled films, as well as 3D network structures. …”
Section: Introductionmentioning
confidence: 99%
“…As a result, XNBR is more suitable for use in harsh environments than NBR. 23 XNBR has been widely used for seals, tubes, sealing gaskets, gloves, etc. 16 In this study, XNBR/CG composites were prepared with mechanical and latex blending methods, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…ANFs have been extensively studied in the fields of battery separators, adsorption filtration, polymer reinforcement, thermal insulation, and flexible electronic devices. ANFs have been extensively studied for their potential to improve the mechanical properties of various polymers, including polyurethane [2][3][4], rubber [5][6][7][8], epoxy resin [9][10][11], polyvinyl alcohol [12], and polypyrrole [13]. For example, Wang et al [6] found that adding 5 wt% of ANFs increased the tensile strength and tear strength of carboxylated acrylonitrile butadiene rubber by 182% and 101%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…ANFs have been extensively studied for their potential to improve the mechanical properties of various polymers, including polyurethane [2][3][4], rubber [5][6][7][8], epoxy resin [9][10][11], polyvinyl alcohol [12], and polypyrrole [13]. For example, Wang et al [6] found that adding 5 wt% of ANFs increased the tensile strength and tear strength of carboxylated acrylonitrile butadiene rubber by 182% and 101%, respectively. Guo et al [13] combined the outstanding mechanical properties of ANFs with the conductivity of polypyrrole to prepare ANF/polypyrrole composite films with excellent electromagnetic shielding, wearable sensing, resistive heating, and photothermal conversion performance.…”
Section: Introductionmentioning
confidence: 99%